Diazepam in acute myocardial infarction. Clinical effects and effects on catecholamines, free fatty acids, and cortisol. - Melsom, M (1976)
Diazepam is a valuable drug in cases of acute myocardial infarction. The 10 mg intravenous loading dose and the subsequent 15 mg oral dose of diazepam administered three times daily produced safe, pleasant sedation, and reduced the need for analgesics. A much reduced excretion of catecholamines was recorded. It is presumed that diazepam causes a lower stress reaction, which is beneficial in diminishing the incidence of malignant arrhythmias and preventing the existing myocardial injury from spreading.